Climate or development: Is ODA diverted from its original purpose? - Axel Michaelowa; Katharina Michaelowa (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2005)
We analyze the interaction of climate and development policy that has taken place since the early 1990s. Increasing dissatisfaction about the results of traditional development cooperation and the appeal of climate policy as a new policy field led to a rapid reorientation of aid flows. At the turn of the century, over 7% of aid flows were spent on greenhouse gas emissions mitigation. However, the contribution of emissions mitigation projects to the central development objective of poverty reduction as specified in the Millennium Development Goals is limited and other project types are likely to be much more effective. Adaptation to climate change can be expected to have higher synergies with poverty alleviation than mitigation, primarily through its impact on health, the conservation of arable land and the protection against natural disasters. An analysis of the Clean Development Mechanism shows that projects addressing the poor directly are very rare; even small renewable energy projects in rural areas tend to benefit rich farmers and the urban population. Use of development aid for CDM projects and / or their preparation via capacity building is thus clearly not warranted.
Keywords: 330; ODA; climate policy; poverty reduction; MDGs; CDM; mitigation; adaptation